PROBLEM OF STUDY OF PSYCHOLOGICAL COMPONENT OF HEALTH PROTECTION COMPETENCE OF FUTURE TEACHERS: SYSTEM APPROACH - Melnyk, Inna (Educological discourse, 2020)
The article is devoted to psychological and pedagogical training of future teachers to professional activity. The main purpose of the article is the selection of a systematic approach to the study of psychological component of health protection competence of future teachers on the basis of summarizing the relevant theoretical sources. Presents a brief theoretical overview of current research on the formation health protection competence of future teachers. Analyzes different approaches to the interpretation of the concept of «health protection competence» in the works of leading Ukrainian and foreign scientists, characterized its components. Filed our own interpretation of the concept of health protection competence as an integral characteristic, including: a deep knowledge of the person about the nature and indicators of the concept of «mental health»; strong motivation and unconditional acceptance of the idea that mental health is extremely important to take care; practical and skills allowing daily care of your mental health; the capacity for introspection and critical to the level of such skills at; the understanding of how these knowledge and skills passed on to younger generations. The article highlights the self a systematic approach to the study of psychological component of health protection competence of future teachers on the basis of criteria - cognitive, motivational and evaluative, activity and reflexive. Defined and characterized the performance of each of these criteria, and also lists the recommended diagnostic tools to study them. The characteristics of the level of development of psychological component of health protection competence of future teachers (high, medium and low), based on the extent to which indicators for each of the selected criteria for the study of psychological component of health protection competence of students. Prospects for development of further empirical research of the psychological component of health protection competence of students of pedagogical specialties. In the future, this information is planned to be used in improving the content of curricula of anthropological disciplines in the first year of pedagogical specialties.